2012
DOI: 10.1111/j.1753-4887.2012.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary aspects of migraine trigger factors

Abstract: The significance of dietary factors as triggers for migraines is controversial, and the assessment of this topic is complex and inconclusive. In order to evaluate the published evidence on dietary triggers, a critical review of the literature was performed by conducting a search for food item descriptors linked to migraines in the PubMed and SciELO databases. Reviews and relevant references cited within the articles that resulted from the search were also included. Of the 45 studies reviewed, 16 were populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 71 publications
(550 reference statements)
0
47
0
2
Order By: Relevance
“…In this case treatment can be initiated by omitting food triggers from the diet (9). Alcohol Although alcoholic beverages are known to trigger headache, the type of beverage is also important for the development of pain (8,34,35). Although not exactly known the mechanism through which alcohol triggers migraine may be associated with ethanol, biogenic amines (histamine, tyramine, phenylethylamine, or others), sulfides, phenolic flavonoids, serotonin release from thrombocytes, or dehydration (33,34).…”
Section: Association With Nutritionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case treatment can be initiated by omitting food triggers from the diet (9). Alcohol Although alcoholic beverages are known to trigger headache, the type of beverage is also important for the development of pain (8,34,35). Although not exactly known the mechanism through which alcohol triggers migraine may be associated with ethanol, biogenic amines (histamine, tyramine, phenylethylamine, or others), sulfides, phenolic flavonoids, serotonin release from thrombocytes, or dehydration (33,34).…”
Section: Association With Nutritionmentioning
confidence: 99%
“…Caffeine causes vasoconstriction and release of stimulating neurotransmitters and stimulates adenosine receptors inside the brain and vessels and blocks their inhibitors (11). A study in young adults and adolescents who had excessive amounts of tea and coffee intake showed an association between coffee consumption and migraine (8). In addition, in the 2 nd edition of the International Classification of Headache Disorders 2 (item; 8.4.1) if caffeine intake in 2 weeks is equal to or more than 200 mg, abrupt cessation of caffeine may also have a triggering effect (39).…”
Section: Caffeinementioning
confidence: 99%
See 2 more Smart Citations
“…A low-fat diet has been shown to reduce headache frequency, intensity, and duration, with subsequently lowered medication use [4]. A recent review identified 16 population studies with data on dietary precipitating factors [5]. Greater than 5% of participants identified specific food triggers in 8 of the studies.…”
Section: Introductionmentioning
confidence: 99%